Chiral optical scattering from helical and twisted silica nanoribbons. Issue 90 (29th October 2021) - Liu, Peizhao; Battie, Yann; Okazaki, Yutaka; Ryu, Naoya; Pouget, Emilie; Nlate, Sylvain; Sagawa, Takashi; Oda, Reiko
Abstract : Helical and twisted silica nanoribbons, deposited in an in-plane direction and with a random orientation, on a quartz substrate showed chiral optical scattering, and helical nanoribbons had a g -factor of the order of 10 −2 below 250 nm. Abstract : Helical and twisted silica nanoribbons, deposited in an in-plane direction and with a random orientation, on a quartz substrate showed chiral optical scattering, and the helical nanoribbons had a g -factor of the order of 10 −2 below 250 nm. Their signs depend on the handedness of the nanohelices. The effect of the morphology and the orientation of the helices on the chiral optical scattering were investigated with simulations via the boundary element method.